Burmese Buddhist Idealism from U Thant to Aung San Suu Kyi. Two Case Studies of Myanmar’s Political Thought - Lubina, Michal (Rethinking Asia in World Politics, 2023)
Myanmar’s Aung San Suu Kyi remains a puzzle. Not a long time ago a global democracy icon, she now faces harsh criticism for her actions in governance. Much has been written about her policies yet there is little attempt to trace the intellectual sources of her policymaking. This article will try to fill this gap by showing that important sources of Suu Kyi’s governing philosophy can be found in 1950s intellectual climate of Burma. Suu Kyi in her political thought follows the (completely forgotten now) tradition of Burmese Buddhist modernists of 1950s whose most famous representative was U Thant. Suu Kyi is quite like them in many regards including the inability to successfully govern a country.